An uncalibrated cylindrical indigenous artefact for measuring inter-axis errors of a five-axis machine tool. Issue 1 (2015) - Mayer, J.R.R.; Rahman, Md. Mizanur; Los, Anna
Abstract: Ever simpler means of monitoring the geometry of five-axis machine tools are required to support automated production lines. This paper investigates the automated probing of the indigenous uncalibrated cylindrical machine table of a five-axis machine tool for estimating its inter-axis error parameters, i.e. the position and orientation errors of its axes. The uncertainties on the estimated errors are calculated from pooled covariance considering the correlation amongst input probing results as obtained from a specially designed series of repeated five daily cycles to distinguish between machine and measurement process variability.